2013
DOI: 10.1186/1475-2867-13-43
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Phf5a/PHF5A and Gja1/GJA1 in rat and human endometrial cancer

Abstract: Endometrial adenocarcinoma is the most frequently diagnosed cancer of the female genital tract in the western world. Studies of complex diseases can be difficult to perform on human tumor samples due to the high genetic heterogeneity in human. The use of rat models is preferable since rat has similarities in pathogenesis and histopathological properties to that of human.A genomic region including the highly conserved Phf5a gene associated to development of EAC has previously been identified in an association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Assessment of PHF5A function enrichment was performed with IPA bioinformatics tools; the two classifications of “Cancer” and “Cell cycle” were significant. This was consistent with previous findings [ 13 , 14 ] and the above experimental data, indicating that PHF5A regulates the cell cycle to participate in tumor development. IGFBP3, PIK3CB, AKT, DDIT3, Skp2, and P53 were subsequently retrieved by the pathway enrichment analysis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Assessment of PHF5A function enrichment was performed with IPA bioinformatics tools; the two classifications of “Cancer” and “Cell cycle” were significant. This was consistent with previous findings [ 13 , 14 ] and the above experimental data, indicating that PHF5A regulates the cell cycle to participate in tumor development. IGFBP3, PIK3CB, AKT, DDIT3, Skp2, and P53 were subsequently retrieved by the pathway enrichment analysis.…”
Section: Discussionsupporting
confidence: 94%
“…These results were further evidenced by TCGA data. Consistent with these findings, Falck et al [ 14 ] found that Phf5a gene expression was significantly increased in endometrial cancer compared with the human benign endometrial tissue, suggesting that expression changes of this gene may be involved in endometrial cancer development. Therefore, we consider that PHF5A may be a potentially highly aggressive and unfavorable prognostic biomarker in LAC.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recent studies in human malignancies, implicated Phf5a in endometrial cancer and glioblastoma 23, 42 . Although Phf5a is suggested to interact with ATP-dependent helicases and the U2 snRNP spliceosome 23, 43 , its silencing surprisingly only affects exon recognition and splicing in glioblastoma stem cells (GSCs) but not their normal counterpart neural stem cells (NSCs) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Gja1 is a connexin shown to be down-regulated in cancer cells and, moreover, connexins have previously been shown to act as tumor suppressors [25,26]. Falck and Karin-Levan (2013) previously found Phf5a/ PHF5Ato be aberrantly expressed in estrogen dependent endometrial adenocarcinoma (EAC) tumors from rat and human type I tumors [27]. Additionally, homologs of Phf5a in Saccharomyces cerevisiae and Schizosaccharomyces pombe have been identified as critical genes in pre-mRNA splicing and cell cycle regulation in these species, as cells lacking this gene showed an arrest in the spliceosome assembly and failed to go through the cell cycle, respectively [11,28].…”
Section: Spliceosome Component Coding Genes Have Previously Been Shownmentioning
confidence: 99%